2021
DOI: 10.1007/s40279-021-01564-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the FIFA 11 + with Added Neck Exercises on Maximal Isometric Neck Strength and Peak Head Impact Magnitude During Heading: A Pilot Study

Abstract: Background Higher neck strength has been postulated to reduce head impact magnitude during purposeful heading in football. Objectives This pilot trial explored the effect of a neck exercise programme on (1) neck strength and (2) head impact magnitude during heading in male and female adolescent football players. Methods Boys and girls (aged 12–17 years) were randomised by team to the intervention (5 weeks of supervised neuromuscular neck exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…8 These findings may indicate that increasing the strength of the neck flexor muscles, thereby increasing the flexor/extensor strength ratio, is key in reducing head acceleration and stabilising the head-neck-torso during impacts to the head or body. 4,12 Earlier research reported that lower neck strength results in increased concussion incidence. 3,4 Intervention programmes that include neck strengthening exercises can decrease the number of head/neck injuries, including concussion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 These findings may indicate that increasing the strength of the neck flexor muscles, thereby increasing the flexor/extensor strength ratio, is key in reducing head acceleration and stabilising the head-neck-torso during impacts to the head or body. 4,12 Earlier research reported that lower neck strength results in increased concussion incidence. 3,4 Intervention programmes that include neck strengthening exercises can decrease the number of head/neck injuries, including concussion.…”
Section: Discussionmentioning
confidence: 99%
“…27,28,29 In footballers, addition of neuromuscular neck exercises to the FIFA 11+ programme was also found to reduce head impact magnitude in adolescents. 12 However, such studies and interventions have focused on increasing neck strength as a whole, not the flexor/extensor strength ratio. Our findings are clinically important as they indicate a need for specific neck training programmes to focus on increasing the neck flexor/extensor strength ratio and subsequent stabilisation of the head on contact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations